The Risk of Thrombosis in Patients with Lupus Anticoagulants Is Predicted by their Specific Coagulation Profile - Galli, Monica; Finazzi, Guido; Norbis, Francesca; Marziali, Stefana; Marchioli, Roberto; Barbui, Tiziano (Thrombosis and Haemostasis, 1999)
Lupus anticoagulants belong to the family of antiphospholipid antibodies. They include two phospholipid-dependent inhibitors of coagulation that may be distinguished on the basis of specific coagulation profiles generated from the comparison of the ratios of the Kaolin Clotting Time (KCT) and the dilute Russell’s Viper Venom Time (dRVVT): when the ratio of the KCT exceeds that of the dRVVT, the plasma is allocated to the “KCT” coagulation profile, when the opposite occurs, the plasma is defined to belong to the “dRVVT” coagulation profile group. We prospectively followed-up a historical cohort of 100 consecutive patients with lupus anticoagulants referred to our Institution between January 1988 and October 1997 to investigate the relationship between their coagulation profile at diagnosis and the development of thrombosis during a median follow-up time of 37.5 months (range 1-115 months). Fifty-six patients were allocated to the “dRVVT” coagulation profile, whereas the other 44 displayed the “KCT” profile. Lupus anticoagulants were transient in 17 patients, without differences between the two groups. None of these patients developed clinical events before disappearance of the phospholipid-dependent inhibitors of coagulation. The 83 cases with persistent lupus anticoagulants consistently displayed the same coagulation profile they had been allocated to at entry. Fourteen patients developed 18 thromboembolic events during the follow-up, with an overall rate of thrombosis of 4.2% patients-year. Twelve of them belonged to the “dRVVT” coagulation profile, whereas the other 2 to the “KCT” profile (p = 0.03). The “dRVVT” coagulation profile gave an odds ratio of thrombosis of 5.25 (95% confidence interval [C.I.]: 1.17-23.50). Ten of the 14 patients who developed thrombosis during follow-up had already experienced thrombosis: a previous thrombotic event caused an odds ratio of recurrency of 2.72 (95% C.I.: 0.85-8.73) (p = 0.09). By multivariate analysis, the “dRVVT” coagulation profile was still associated with a trend to a higher risk of thrombosis, but the difference did not reach statistical significance. Increased levels of anticardiolipin antibodies (> 40 GPL and/or MPL units) were found in all the 14 patients (p = 0.0064). The “KCT” coagulation profile was significantly associated (p = 0.005) with moderate thrombocytopenia (platelets 50-150 × 109/l). Neither profile was found to represent a risk factor for the development of recurrent miscarriages, neoplastic diseases and death. In conclusion, the “dRVVT” profile appears to have predictive value with respect to the thrombotic complications suffered by patients with antiphospholipid antibodies.